Withdrawal notice to "40-Year incidence of early-onset Parkinson's disease (EOPD) in Southeast Minnesota" [Park. Relat. Disord. 104 (2022) 64–67]. (February 2023) - Camerucci, Emanuele; Mullan, Aidan F.; Turcano, Pierpaolo; Stang, Cole D.; Bower, James; Savica, Rodolfo
Abstract : This article has been withdrawn at the request of the editor and publisher. The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error. The full Elsevier Policy on Article Withdrawal can be found at (https://www.elsevier.com/about/policies/article-withdrawal ).